Analisis Manajemen Strategi pada UMKM “Warmindo Mabar Café” menggunakan Analisis Swot dan Matriks QSPM - Gani Pardiansah; Sharma Rodiah; Rara Alma Novalia Asmara; Muhammad Irfan; Fajri Zhahiran; Ridlwan Muttaqin (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2026)
This study aims to analyze strategic management at the Warmindo Mabar Cafe MSME using SWOT analysis and the QSPM Matrix. Warmindo Mabar Cafe is a culinary business established in 2022 in Bandung City with a primary target market of students. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation of the owner, employees, and consumers. Data were analyzed using the IFE Matrix, EFE Matrix, IE Matrix, TOWS Matrix, and the Quantitative Strategic Planning Matrix (QSPM). The analysis results show that the internal condition of the business is in a fairly strong position with an IFE value of 2.76, while external conditions show good responsiveness with an EFE value of 2.81. Based on the IE Matrix, Warmindo Mabar Cafe is in Cell V (Growth Stability) which suggests a stable growth strategy. The results of the QSPM analysis show that the product development strategy obtained the highest Total Attractiveness Score (TAS) of 6.77, making it a top priority strategy. Recommended strategies include digital marketing, entertainment facility-based branding, product bundling development, weekend activations, and operational efficiency.